2021
DOI: 10.1109/tpel.2020.3012298
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BTI-Induced Threshold Voltage Shifts in Shoot-Through Currents From Crosstalk in SiC MOSFETs

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In [33], it has shown that the crosstalk shoot-through current could be used as a parameter to characterize devices subject to Bias Temperature Instability (BTI). The experiment is also performed to reveal the impact of BTI on three selected DUTs with the testing circuit and experiment procedure described in Fig.…”
Section: F Impact Of Bti On Shoot-through Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…In [33], it has shown that the crosstalk shoot-through current could be used as a parameter to characterize devices subject to Bias Temperature Instability (BTI). The experiment is also performed to reveal the impact of BTI on three selected DUTs with the testing circuit and experiment procedure described in Fig.…”
Section: F Impact Of Bti On Shoot-through Currentmentioning
confidence: 99%
“…The combination of top and bot gate resistance (R G_T op and R G_Bot ) are 47 Ω and 330 Ω, respectively. It is necessary to intentionally have large R G_Bot or the impact of BTI may not be revealed [33]. In this experiment, the DUT at bottom is stressed before the turn-ON of top device to initiate crosstalk.…”
Section: F Impact Of Bti On Shoot-through Currentmentioning
confidence: 99%
“…However, there are few literatures on crosstalk issue under resistive load. In [20] and [24], only the crosstalk experiments were carried out with resistive load. Therefore, it is necessary to establish an analytical model of crosstalk voltage under resistive load, and then quantitatively analyze the influence of various parameters on the crosstalk voltage under resistive and inductive load to ensure the reliable operation of devices.…”
Section: Introductionmentioning
confidence: 99%
“…This was defined as a maximum of 24 hours for silicon devices but has been redefined as 96 hours for SiC MOSFETs [8] and largely remains unclear for GaN e-HEMTs. VTH shift from VGS stress has been studied extensively in SiC MOSFETs [9][10][11] and is increasingly being studied in GaN e-HEMTs [12,13].…”
Section: Introductionmentioning
confidence: 99%